Hugh of St Victor, Isaiah’s Vision, and De arca Noe - Grover, A. Zinn (Studies in church history, 1992)
Hugh of St Victor’s two treatises on Noah’s Ark, De arca Noe morali and De arca Noe mystìca, are major twelfth-century writings on the contemplative life with a significant relationship to the medieval iconographie tradition. Both refer to a drawing that symbolically presents the spiritual teaching of the treatises. Unfortunately this drawing no longer exists, but De arca Noe mystica describes it in detail. That description and passages in De arca Noe morali show that the drawing had three major iconographie elements:(1) a figure of Christ ‘seated in majesty’ as seen in a vision by the prophet Isaiah (Isaiah 6);(2) a symbolic cosmos, with the earth at the centre, surrounded by the regions of aer and aether; and(3) a schematized drawing of Noah’s Ark, depicting it as a three-storeyed, pyramidal vessel viewed from above.These three ‘units’ were arranged so that the figure of Christ held the symbolic cosmos in front of his body (with only his head, hands, and feet visible), while the diagram of the Ark was placed in the centre of the symbolic cosmos so that the earth surrounded the Ark.